Autonomic activity, frailty phenotype and risk of falling in the elderly: Study protocol - Arantes, Flávia Sousa; Oliveira, Miriã Cândida; Arantes Souza, Shayra Kellen; Nóbrega da Silva Nunes, Carla; Ribeiro Afonso, João Pedro; Pimentel Aleluia Freitas Júnior, Adonay; Lima Rodrigues, Glauco; Cezar da Silva Correia, Kassio; Costa, Eva Vívian; Pinna, Lucas; Ferreira da Silva, Gislene; Kelly da Palma, Renata (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: Generally, in the aging process, there is degradation of autonomic nervous control mechanisms, compromising the regulation of heart rate, which contributes to increased frailty and the risk of falls. This process is defined as a geriatric syndrome that leads to impairment of physiological systems and homeostatic imbalance. Objective: To correlate heart rate variability (HRV), frailty parameters, and the risk of falls in elderly people from a community center. Methods: This research will involve active seniors and participants from the Centro de Convivências de Praia Grande, São Paulo, Brazil. Clinical, demographic, and anthropometric data, psychological variables, and physical conditions will be collected through the International Physical Activity Questionnaire (IPAQ) and the risk of falls test. The heart rate R-R intervals will be analyzed using the H10 polar frequency meter and the HRV application, and transferred to the Kúbios software for further analysis.Results: Two hundred and fourteen participants are involved in this study, 181 (84.6%) of whom are female, 137 (64.0%) are white, with a mean age of 70.27 ± 7.07 years, a weight of 68.37 ± 11.15 kg, and a body mass index of 27.04 ± 4.04 kg/m2. Conclusion: A positive correlation is expected through the stratified analysis of frailty indices, risk of falls, and HRV, suggesting that the lower the HRV, the greater the risk of falls and the greater frailty in the elderly.